Necesidad de reformar el art. 7 de la Ley Orgánica de garantías jurisdiccionales y control constitucional, con la finalidad de que en los procesos constitucionales se radique la competencia de las juezas y jueces competentes en la materia, únicamente mediante el sorteo correspondiente - Hartwig Carranza, Kurt Patricio (2015)
Our country is going through a juridical transformation; in which, all law subjects are constantly evolving with the intention of aiming equality, efficiency, and effectively when applying the law in all social sectors of Ecuador. So much is done that there are new regulations and some others under revision wail for their approbation. Because our country is constitutional, it is fundamental that there are regulations to accomplish the sense of justice; it will guarantee the enforcement of rights established in the Republic of Ecuador Constitution. The Organic Law for Judicial Warranty and Control Constitutional is the statute that will guarantee the awareness of rights and their protection system. It is been developed a research to determine the fallacies that are present during the execution of the above named law. During this research, after a deep understanding of the legislation compared to an extensive analysis of surveys and interviews to a considerable group of professionals in the Law industry, special focus in judges in the Judicial Penal and Transit Department and judges in the Judicial Department for the Violence against Women and Family in the Santo Doming Province; we were able to determine that in reality the application of the last Art 7 of the Law for Guaranties of Jurisdiction and Control Constitutional is not allowing that all processes that are initiated during non-business days are receiving an equal process as the same processes that are initiated during business days. This contradicts what is established in bullet 3 of article 8 of The Organic Law for Judicial Warranty and Control Constitutional; which reads that all “days and hours are considered working business days.” This is also reflected in bullet 3 of article 86 of the Ecuadorian Republic Constitution. The creation of new departments and units and the increment of Judges in Ecuador, with the objective of accomplishing a faster execution of the law has not helped in keeping all processes up to date; such circumstances have allowed the need to replace the last bullet of Article 7 before mentioned